Muscle–brain crosstalk mediated by exercise-induced myokines - insights from experimental studies - Kostka, Magdalena; Morys, Julia; Małecki, Andrzej; Nowacka-Chmielewska, Marta (Frontiers in Physiology, 2024)
Over the past couple of decades, it has become apparent that skeletal muscles might be engaged in endocrine signaling, mostly as a result of exercise or physical activity in general. The importance of this phenomenon is currently studied in terms of the impact that exercise- or physical activity -induced signaling factors have, in the interaction of the “muscle-brain crosstalk.” So far, skeletal muscle-derived myokines were demonstrated to intercede in the connection between muscles and a plethora of various organs such as adipose tissue, liver, or pancreas. However, the exact mechanism of muscle-brain communication is yet to be determined. It is speculated that, in particular, brain-derived neurotrophic factor (BDNF), irisin, cathepsin B (CTSB), interleukin 6 (IL-6), and insulin-like growth factor-1 (IGF-1) partake in this crosstalk by promoting neuronal proliferation and synaptic plasticity, also resulting in improved cognition and ameliorated behavioral alterations. Researchers suggest that myokines might act directly on the brain parenchyma via crossing the blood-brain barrier (BBB). The following article reviews the information available regarding rodent studies on main myokines determined to cross the BBB, specifically addressing the association between exercise-induced myokine release and central nervous system (CNS) impairments. Although the hypothesis of skeletal muscles being critical sources of myokines seems promising, it should not be forgotten that the origin of these factors might vary, depending on the cell types engaged in their synthesis. Limited amount of research providing information on alterations in myokines expression in various organs at the same time, results in taking them only as circumstantial evidence on the way to determine the actual involvement of skeletal muscles in the overall state of homeostasis. The following article reviews the information available regarding rodent studies on main myokines determined to cross the BBB, specifically addressing the association between exercise-induced myokine release and CNS impairments.